AI based scheme on voice service quality evaluation and assurance - Guangyu LI; Yanping LIANG; Li YU; Kun WANG; Yangming CHEN; Sijia LIU (Dianxin kexue)
The voice service is one of the mainstream services under the telecommunications network.The mainstream voice service quality evaluation method in the industry is to compare the voice and audio of the transceiver and calculate the POLQA MOS, which is the standard benchmark for voice quality analysis.For telecom operators, perceive voice service quality efficiently without any infringement of user privacy, and carry out precise service quality assurance, is one of the key tasks.A system using mathematical statistics and neural network to learn the mapping between voice service feature data from network side and voice quality from user side to generate evaluation model with high accuracy and precision was proposed.On this basis, the system made use of data information from multiple fields including wireless network user level and cell level, to analyze reasons and work out solutions for poor service quality, so as to assure service quality efficiently and accurately.The result shows that the scheme has achieved good practical application results.